Design Of A Mobile App-Based Student Scout Extracurricular Activity Monitoring Application Using Geotagging: Case Study At A Junior High School In Bandung - Fitri Rizqiati (JURNAL COMPUTECH & BISNIS, 2025)
Teachers have a responsibility to monitor students, particularly given the constraints in supervising them during extracurricular activities such as scouting.  This research aims to develop a mobile application to track student engagement in scouting activities, employing a descriptive-qualitative methodology through data collection via observation, interviews, and literature reviews.  The application is built on the AppSheet online platform and integrates with Google Drive as a database, using spreadsheets for data management.  The research findings demonstrate that a student monitoring application is crucial for individual and institutional requirements.  For future development, the application must be designed for simplicity to ensure accessibility for all users, with data presented in a manner that is comprehensible to educators.